Changes in gastronomy - Burešova, Pavla; Mrkvova, Katarina; Dudić, Branislav (Hotel and Tourism Management, 2020)
The paper provides an insight into factors influencing developments in gastronomy and catering services. The aim of the text is to identify the key elements affecting contemporary catering services including attendance at catering establishments, preferences in food selection, use of lunch menus, and adherence to hygiene standards in operational practice in food production. The first part of the survey shows the issue of restaurant attendance during the working week. The second part examines the frequency of restaurant visitors, restaurant attendance at weekends and also the factors that influence the choice of food. The representative sample consists of the Czech National Panel, with respondents above 15 years of age. The data were obtained from 504 respondents (N 504). The third part of the investigation meets the most important criteria that affect the quality of services – hygiene standards in gastronomy focused on compliance with hygiene standards from the perspective of hygiene control authorities. Factors for deciding the choice of food in restaurants and the frequency of restaurant visits were also examined.